Analisis Pengaruh Service Quality dan Brand Image terhadap Purchase Decision dengan Customer Satisfaction sebagai Variabel Intervening - Langgeng Putri Melinda; I Made Bayu Dirgantara (Diponegoro Journal of Management, 2025)
In an era of increasingly competitive business competition, companies are required to rely not only on product quality, but also on service quality and strong brand image to influence consumer purchasing decisions. This study aims to analyze the effect of service quality and brand image on purchase decisions with customer satisfaction as an intervening variable. This study uses a quantitative approach with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique through SmartPLS software. The population in this study were consumers who used services at one of the XYZ service companies, with a sample of 120 respondents taken using purposive sampling techniques. The variables in this study consisted of service quality (X1), brand image (X2), customer satisfaction (Z), and purchase decision (Y). Data collection was carried out through a questionnaire with a Likert scale of 1–5. The results of the outer model analysis showed that all indicators met the criteria for convergent validity (loading factor> 0.7), construct reliability (composite reliability> 0.7), and discriminant validity (AVE> 0.5). Meanwhile, the results of the inner model test show that service quality and brand image have a positive and significant effect on customer satisfaction, and customer satisfaction has a significant effect on purchase decisions. However, service quality and brand image do not have a direct effect on purchase decisions. Customer satisfaction is proven to partially mediate the influence of both variables on purchasing decisions. This study concludes that service quality and brand image will have a greater impact on purchasing decisions if accompanied by high customer satisfaction. Therefore, companies are advised to focus on creating a satisfying customer experience in order to increase loyalty and repurchase intentions.